Role of Notary in Murabahah Transactions in Syariah Banks - Sunaryo Sunaryo (Sultan Agung Notary Law Review, 2020)
The formulation of the problem in this research is how the role of the notary in implementation of the Murabahah financing contract in Sharia Banks and what are the obstacles to the role of a notary in completing a Murabahah financing contract at a Sharia Bank.The results of this study indicate that the notary has a different role when partnering Islamic banks. In his role, the notary is in charge of making Murabahah financing deeds at the sharia bank. Another role, the notary public also plays a role during dealings with people for the sake of whose notary deed was drawn up. In addition to people, there is also a place of position as the deed maker.